Influence of Boulder Concentration on Turbulence and Sediment Transport in Open‐Channel Flow Over Submerged Boulders. Issue 12 (19th December 2017) - Fang, H. W.; Liu, Y.; Stoesser, T.
Abstract: In this paper the effects of boulder concentration on hydrodynamics and local and reach‐averaged sediment transport properties with a flow over submerged boulder arrays are investigated. Four numerical simulations are performed in which the boulders' streamwise spacings are varied. Statistics of near‐bed velocity, Reynolds shear stresses, and turbulent events are collected and used to predict bed load transport rates. The results demonstrate that the presence of boulders at various interboulder spacings altered the flow field in their vicinity causing (1) flow deceleration, wake formation, and vortex shedding; (2) enhanced outward and inward interaction turbulence events downstream of the boulders; and (3) a redistribution of the local bed shear stress around the boulder consisting of pockets of high and low bed shear stresses. The spatial variety of the predicted bed load transport rate q s based on local bed shear stress is visualized and is shown to depend greatly on the boulder concentration. Quantitative bed load transport calculations demonstrate that the reach‐averaged bed load transport rate may be overestimated by up to 25 times when including the form‐drag‐generated shear stress of the immobile boulders in the chosen bed load formula. Further, the reach‐averaged bed load transport rate may be underestimated by 11% if the local variability of the bed shear stress is not accounted for. Finally, it is shown that for the small‐spaced boulder array, the bed load transport rates should no longer be predicted using a normal distribution with standard deviation of the shear stress distribution σ . Key Points: The presence of large immobile boulders significantly influences the flow and turbulence field in the vicinity of submerged boulders The boulder concentration plays an important role in forming skimming to isolated roughness flows and predicting bed load transport rates The bed load transport rate will be underestimated when using the reach‐averaged shear stress, compared with that based on local shear stress